The Relationship Between Feeding Patterns, Parental Knowledge, and Compliance with Visits to the Integrated Health Post (Posyandu) and the Nutritional Status of Toddlers at the Integrated Health Post (Posyandu) in Parungmulya Village in 2025 - Rofiqoh; Sudiono; Saleh Budi Santoso (INDOGENIUS, 2026)
Background & Objective: Nutritional status issues can have serious impacts on children's growth and development, both physically and cognitively. This study aims to determine the relationship between feeding patterns, parental knowledge, and adherence to visits to the integrated health post (Posyandu) with the nutritional status of toddlers at the Integrated Health Post (Posyandu) in Parungmulya Village in 2025. Method: This study used a cross-sectional approach. The sample size was 82 respondents. The research instruments were questionnaires and anthropometric measurements with BB/U indicators. Data analysis used Chi-Square. Result: The results showed that most respondents had appropriate feeding patterns (70.7%), good parental knowledge (59.8%), adherence to visiting the integrated health post (52.4%), and toddler nutritional status in the normal weight category (74.4%). Conclusion: There was a significant relationship between feeding patterns and toddler nutritional status with (p-value 0.000), between parental knowledge and toddler nutritional status with (p-value 0.000), and between attendance at integrated health post (Posyandu) visits with toddler nutritional status with (p-value 0.022). The results of this study are expected to be a reference for improving education and interventions to maintain optimal toddler nutritional status.